Beginning fedora desktop : Fedora 20 Edition - Petersen, Richard (Apress, 2014)
Beginning Fedora Desktop: Fedora 20 Edition is a complete guide to using the Fedora 20 Desktop Linux release as your daily driver for multimedia, productivity, social networking, the GNOME 3 desktop, administrative tasks, and more. Author and Linux expert Richard Petersen delves into the operating system as a whole and offers you a complete treatment of Fedora 20 Desktop configuration and use. You'll discover how to install and update the Fedora 20 Desktop, learn which applications perform which functions, how to manage software, use of the GNOME 3 and KDE desktop configuration tools, useful shell commands, and both the Fedora administration and network tools. Get the most out of Fedora 20 Desktop -- including free Office suites, editors, e-book readers, music and video applications and codecs, email clients, Web browsers, FTP and BitTorrent clients, microblogging and IM applications -- with a copy of Beginning Fedora Desktop: Fedora 20 Edition at your side.